What innovative practices and processes are used to deliver psychosocial care in India? A qualitative case study of three non-profit community mental health organisations - Varadharajan Srinivasan; Sumeet Jain; Winston Kwon; Clement Bayetti; Anish V. Cherian; Kaaren Mathias (Elsevier, 2023)
The global mental health field seeks to close the "treatment gap" for mental illness in low-and middle-income countries by scaling evidence-based interventions. The evidence base has often bypassed psychosocial interventions by local organizations who do not fit a biomedical approach to evidence building. In India, non-profit mental health organizations are addressing care gaps through novel approaches that emphasize social recovery and inclusion.This study seeks to better understand the nature and dynamic of this innovation by examining what was working well in the practices and processes of three such community mental health care organizations. A comparative case approach was chosen for its strength as an exploratory means for inductive theory building. Three case organizations in Kerala, West Bengal and Uttarakhand states were selected based on their diverse socio-cultural and health systems settings. Qualitative data was collected in 2018-20, to examine their practices and processes using mixed methods and data sources including interviews, focus groups, participant observation and document analysis.Common strategies observed across the three organizations, included engaging community, prioritising beneficiaries, co-opting resources, devolving care, reorganising communication and recovery and integration. These strategies were further categorized into three domains: constructing a sustainable resource base, managing knowledge and redefining meanings. In contrast with conventional problem-solving approaches, these cases used an approach that built on assets and strengths using inclusive governance which enabled coordination of the community health system.This study argues that these organizations incorporate reflexive practice and two-way flows of knowledge to enable them to address complex social determinants of mental health. This has implications for how psychosocial care in CMH is conceptualized. We argue that the ways the organizations respond to the complexities of mental health difficulties contributes to reframing mental health as a social development issue, centering inclusion of people with psychosocial disabilities. Our findings argue against a polarization between biomedical and psychosocial CMH models and illustrate ways of integrating both approaches and their centrality to effective mental health care.